Brain-Derived Neurotrophic Factor and Major Depressive Disorder: Evidence from Meta-Analyses - Kishi, Taro; Yoshimura, Reiji; Ikuta, Toshikazu; Iwata, Nakao (Frontiers in Psychiatry, 2018)
Accumulating evidence suggests that brain-derived neurotrophic factor (BDNF) is associated with the pathophysiology of major depressive disorder (MDD). In this mini review, we explored the association between BDNF and MDD using meta-analytic evidence. Our findings indicated that the Val66Met polymorphism in the BDNF gene was not associated with MDD or hippocampal volume in patients with MDD. However, plasma/serum levels of BDNF were decreased in patients with acute MDD compared with healthy controls. Both antidepressant treatment and electroconvulsive therapy increased plasma and serum levels of BDNF in patients with MDD. Val66Met polymorphism in the BDNF gene was associated with an antidepressant response in patients with MDD. Taken together, we did not detect any plausible evidence regarding Val66Met polymorphism in the BDNF gene contributing to a risk of MDD. However, peripheral BDNF levels are decreased in patients with MDD, and the polymorphisms are associated with treatment response. However, BDNF is best understood to be a biomarker for the state of MDD and its treatment response rather than a risk factor for MDD.